Intestinal Tuberculosis Masquerading as Crohn’s Disease? A Case of Disseminated Tuberculosis after Anti-TNF Therapy for Suspected Crohn’s Disease - Alexander P. Abadir; James Y. Han; Fady A. Youssef (Case Reports in Gastrointestinal Medicine)
Intestinal tuberculosis (ITB) and Crohn’s disease (CD) very closely resemble each other in symptomatology, imaging, appearance, and pathology. While ITB is rare in the United States, its prevalence is significantly higher in endemic areas, thus presenting a diagnostic dilemma in immigrant populations from high-risk countries. This patient was diagnosed with CD and treated with anti-TNF agents after indeterminate screening for latent tuberculosis. He was then admitted with septic shock and intestinal perforation due to disseminated tuberculosis. This case demonstrates the importance the consideration of ITB when a patient with risk factors for TB fails to respond to treatment for CD.